Microdisk array based Weyl semimetal nanofilm terahertz detector - Song, Qi; Zhou, Zhiwen; Zhu, Gangyi; Liang, Huawei; Zhang, Min; Zhang, Bingyuan; Liu, Fang; Yan, Peiguang (Nanophotonics (Berlin, Germany), 2022)
High-performance terahertz wave detectors at room temperature are still urgently required for a wide range of applications. The available technologies, however, are plagued by low sensitivity, narrow spectral bandwidth, complicated structure, and high noise equivalent power (NEP). Here, we have demonstrated a Weyl semimetal surface plasmon-enhanced high-performance terahertz wave detectors which are based on microdisk array deposited WTe nanofilm epitaxially grown on GaN substrate for room temperature operation. With the microdisk array combined the WTe layer, strong terahertz wave surface plasmon polaritons can be generated at the WTe –air interfaces, which results in significant improvement in detecting performance. For the 40 μm diameter microdisk array, a detectivity ( ) of 5.52 × 10 cm Hz pW at 0.1 THz is achieved at room temperature. In addition, the responsivity ( ) of 8.78 A W is also obtained. Such high-performance millimeter and terahertz wave photodetectors are useful for wide applications such as high capacity communications, walk-through security, biological diagnosis, spectroscopy, and remote sensing.